Immune responses to hair dyes containing toluene‐2, 5‐diamine. (18th February 2014) - Schmidt, J.D.; Johansen, J.D.; Nielsen, M.M.; Zimersson, E.; Svedman, C.; Bruze, M.; Engkilde, K.; Poulsen, S.S.; Geisler, C.; Bonefeld, C.M.
Summary: Background: Toluene‐2, 5‐diamine (PTD) is the most frequently used dye in oxidative hair dyes on the Scandinavian market. However, little is known about immune responses to PTD‐containing oxidative hair dyes. Objectives: To study immune responses induced by PTD‐containing hair dyes in mice. Methods: Immune responses against two different permanent hair dye products containing 1·60% (w/w) and 0·48% (w/w) PTD within the colour gel, and various concentrations of pure PTD were studied. The local inflammatory response was measured by ear swelling and cell infiltration, and T‐ and B‐cell infiltration and proliferation was determined in the draining lymph nodes. Results: Concentration‐dependent immune responses were seen to PTD both in the skin and draining lymph nodes. The hair dye containing 1·60% PTD induced strong local inflammation and caused T‐ and B‐cell infiltration and proliferation as well as an increased number of regulatory T cells in the draining lymph nodes. In contrast, the hair dye containing 0·48% PTD induced skin inflammation but only minor responses in the draining lymph nodes. Conclusions: Consumer‐available PTD‐containing permanent hair dyes can be potent immune activators inducing both pro‐ and anti‐inflammatory responses. The outcome of the response is dependent on allergen dose, amount of additional allergens and exposure regime. Abstract : What's already known about this topic? Use of permanent hair dyes can induce severe contact allergic reactions. Toluene‐2, 5‐diamine (PTD) is more frequently used in hair dyes in the Scandinavian market than p ‐phenylenediamine (PPD). What does this study add? PTD‐containing consumer‐available hair dyes can induce severe immunological reaction in mice. The immune response to PTD‐containing hair dyes is dependent on PTD concentration and additional allergens within the hair dye mixture.